Using the Greater Tuberosity as a Reference for Placement of Proximal Humerus Plates Leads to a High Rate of Calcar Screw Malposition. Issue 10 (October 2022) - Patel, Midhat; Castaneda, Paulo; Kisana, Haroon; Roache, William K.; Dehghan, Niloofar; McKee, Michael D.; Amini, Michael H.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Achieving calcar fixation is critical to minimize the failure of proximal humerus fractures repaired with proximal humeral locking plates (PHLPs). Many operative technique manuals reference the greater tuberosity (GT) for plate placement. The objective of this study was to examine the accuracy of calcar screw placement when PHLPs were placed based on distance from the GT. Methods: Twenty cadaveric specimens were acquired representing a height distribution across the US population. Thirteen different PHLPs were applied. A drill bit was placed through the designated calcar screw hole and measured on radiographs, with the inferior 25% of the head representing an ideal placement. Results: Three hundred fifty constructs were studied. In 28% of the specimens, the calcar screw was misplaced. In 20% of the specimens, it was too low, whereas in 8%, it was too high. The calcar screw missed low in 30% of patients shorter than 5 feet, 5.5 inches versus 8% of taller patients ( P = 0.007). It missed high in 13% of taller patients versus 2% of shorter patients ( P = 0.056). Calcar screws in variable-angle plates missed 0% of the time, whereas those in fixed-angle plates missed 36% of the time ( P = 0.003). Conclusions: Placement of PHLPs based on distance from the GT results in unacceptable position of the calcar screw 28% of the time and up to 36% in fixed-angle plates. This could be further compounded if the GT is malreduced. Current technique guide recommendations result in an unacceptably high rate of calcar screw malposition.